An integrative review of the qualities of a 'good' physiotherapist. (2nd January 2023) - Kleiner, Michelle J.; Kinsella, Elizabeth Anne; Miciak, Maxi; Teachman, Gail; McCabe, Erin; Walton, David M.
ABSTRACT: Introduction: Qualities of a physiotherapist may influence the therapeutic alliance and physiotherapy outcomes. Understanding what qualities constitute a 'good' physiotherapist has yet to be systematically reviewed notwithstanding potentially profound implications for the future practice of physiotherapy. Purpose: The primary purpose of this review was to critically examine how physiotherapists and their patients describe the qualities of a 'good' musculoskeletal physiotherapist as depicted in peer-reviewed literature. The secondary aim was to synthesize qualities represented in the literature, and to compare patient and physiotherapist perspectives. Methods: An integrative review methodology was used to undertake a comprehensive literature search, quality appraisal of studies, and thematic analysis of findings. An electronic search of CINAHL, EMBASE, Nursing and Allied Health, PsycINFO, PubMed, and Scopus databases was conducted within a time range from database inception to June 14, 2019. Results: Twenty-seven studies met the inclusion criteria. Six qualities of a 'good' musculoskeletal physiotherapist were identified as: responsive, ethical, communicative, caring, competent, and collaborative. Conclusions: The qualities of a 'good' physiotherapist identified in the review emphasize the human interaction between physiotherapists and patients and point to the centrality of balancing technical competence with a relational way of being.